Students’ Perception on Online Arabic Learning Based on Learning Principle of Rusydi Ahmad Thu’aimah Perspective: Case Study in Arabic Language Intensive Program of State Islamic University of Sunan Ampel Surabaya - Asma Nafiesatinnaja; Muhammad Thohir; Muhammad Afifudin Dimyathi (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2022)
Arabic language learning must experience its learning system reconstruction as a consequence of Covid-19 pandemic which hits the world globally. The system change from offline to online makes each learning component must adjust with new system by still referring to the learning principles built adjusting with the virtual system. This article presents the study result conducted on Arabic language program at State Islamic University of Sunan Ampel Surabaya. The purpose of this research was to understand the students’ perception about online Arabic language learning based on the learning principle by Rusydi Ahmad Thu’aimah which covers communication principle, learning method principle, and learning media principle. This study was conducted by using qualitative method through case study approach with data obtained through questionnaire based survey strengthened by the data of interview result. The research result showed that students had quite good perception on Arabic language intensive learning in odd semester of 2021-2022.